2021
DOI: 10.7554/elife.66454
|View full text |Cite
|
Sign up to set email alerts
|

Hybrid protein assembly-histone modification mechanism for PRC2-based epigenetic switching and memory

Abstract: The histone modification H3K27me3 plays a central role in Polycomb-mediated epigenetic silencing. H3K27me3 recruits and allosterically activates Polycomb Repressive Complex 2 (PRC2), which adds this modification to nearby histones, providing a read/write mechanism for inheritance through DNA replication. However, for some PRC2 targets, a purely histone-based system for epigenetic inheritance may be insufficient. We address this issue at the Polycomb target FLOWERING LOCUS C (FLC) in Arabidopsis thaliana, as a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
20
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
4

Relationship

2
8

Authors

Journals

citations
Cited by 28 publications
(25 citation statements)
references
References 66 publications
2
20
0
Order By: Relevance
“…The analog autonomous pathway component of FLC regulation controls transcription through an FCA-mediated mechanism. Based on previous studies on the interplay between transcription and PRC2 silencing (Beltran, Yates et al 2016, Berry, Dean et al 2017, Holoch, Wassef et al 2021, Lövkvist, Mikulski et al 2021), we propose that digital Polycomb silencing is prevented by high transcription in fca-1 , while low transcription is not sufficient to significantly oppose silencing in Ler. In fca-3 , the dynamical antagonism between Polycomb silencing and an intermediate level of transcription is still ongoing at our experimentally accessible timepoints.…”
Section: Discussionmentioning
confidence: 88%
“…The analog autonomous pathway component of FLC regulation controls transcription through an FCA-mediated mechanism. Based on previous studies on the interplay between transcription and PRC2 silencing (Beltran, Yates et al 2016, Berry, Dean et al 2017, Holoch, Wassef et al 2021, Lövkvist, Mikulski et al 2021), we propose that digital Polycomb silencing is prevented by high transcription in fca-1 , while low transcription is not sufficient to significantly oppose silencing in Ler. In fca-3 , the dynamical antagonism between Polycomb silencing and an intermediate level of transcription is still ongoing at our experimentally accessible timepoints.…”
Section: Discussionmentioning
confidence: 88%
“…Finally, epigenetic inheritance in bistable epigenetic regions often requires silencers or other protein-based memory elements (8, 13, 43) in addition to positive feedback. Interestingly, a recent study in budding yeast by (8) showed that the degree of bistability depends on both the degree of nucleation at silencers and positive feedback via recruited nucleosome conversions.…”
Section: Resultsmentioning
confidence: 99%
“…This could be tested by observing the fate of artificial ectopic mark domains of different lengths [34, 53, 54]. Very small domains that appear to exhibit a cis -memory of silencing [55] may rely on alternative mechanisms [56].…”
Section: Discussionmentioning
confidence: 99%